Analysis of Tourist Attraction Objects (ODTW) Case Study Pamah View, Kec. Sei Bingai, Langkat Regency, North Sumatra - Saqina, Dilvia; Sibuea, Tracy Ocha Yulia; Aceh, Resty Marhamah; Mahdariani; Azhar, Muamar; Sugiharto; Permana, Sendi (Future Space: Studies in Geo-Education, 2024)
This research aims to determine the effect of tourist attractions on tourist satisfaction at the Pamah View tourist attraction in Langkat district. The reason researchers researched the Pamah View area was because its location was quite strategic and it didn't take much travel time to get to this location. This study employs qualitative research methods with a descriptive approach. Descriptive research is a research method that attempts to describe the object or subject being studied according to what it is, with the aim of systematically describing the facts and characteristics of the object being studied accurately. In accordance with the results of research that has been carried out, the Pamah View tourist attraction is located in Kec. Sei Bingai, Langkat Regency, North Sumatra has the most prominent tourist attraction at this location, namely an existing artificial waterfall that has been validated by the management and also visitors who come to the location. The attraction of the building can be seen from the presence of cabins, huts, cafes and other buildings, which is the attraction of the building to attract visitors to come there and is equipped with tents for camping to enjoy the natural beauty there. The socio-cultural attraction of this location can only be seen from the cultural aspects offered at the Pamah View destination which adopts foreign culture, namely Korean culture by providing hanbok costume rental services that can be used by visitors.